2013
DOI: 10.1109/tetc.2013.2274797
|View full text |Cite
|
Sign up to set email alerts
|

Gender-Driven Emotion Recognition Through Speech Signals For Ambient Intelligence Applications

Abstract: This paper proposes a system that allows recognizing a person's emotional state starting from audio signal registrations. The provided solution is aimed at improving the interaction among humans and computers, thus allowing effective human-computer intelligent interaction. The system is able to recognize six emotions (anger, boredom, disgust, fear, happiness, and sadness) and the neutral state. This set of emotional states is widely used for emotion recognition purposes. It also distinguishes a single emotion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 81 publications
(40 citation statements)
references
References 33 publications
(49 reference statements)
0
39
0
1
Order By: Relevance
“…Other works, such as [5] employ the RelAtive SpecTral Amplitude (RASTA) coefficients and the Perceptual Linear Prediction (PLP) coefficients. As reported in [2], an increase in classication performance would usually be expected when more features are used. In addition, if the features number grows, more computations and energy will be needed by the smartphone to carry out the feature set.…”
Section: A Front-end and Feature Extractionmentioning
confidence: 73%
See 2 more Smart Citations
“…Other works, such as [5] employ the RelAtive SpecTral Amplitude (RASTA) coefficients and the Perceptual Linear Prediction (PLP) coefficients. As reported in [2], an increase in classication performance would usually be expected when more features are used. In addition, if the features number grows, more computations and energy will be needed by the smartphone to carry out the feature set.…”
Section: A Front-end and Feature Extractionmentioning
confidence: 73%
“…The human voice y(t) is acquired (with a sample frequency F s = 8 [KHz]) by the smartphone's microphone and it is filtered with a second-order Butterworth BPF with bandwith B ∈ [50, 500] [Hz]. Since the speech signal is not long-term stationary, it is very common to divide the signal into short segments called frames, during which the speech signal can be considered as stationary [2]. In our case, each frame has a length of T = 40 [ms] and frames are overlapped for one third of their duration.…”
Section: The Proposed Spectra Applicationmentioning
confidence: 99%
See 1 more Smart Citation
“…The speaker's gender plays a significant role, since both genders have significantly different vocal features and may express their emotions differently. At an attempt to investigate such issues, Bisio et al [19] demonstrated that the a-priori knowledge of gender may lead to a significant increase of performance, thus they proposed a system whose initial step was to classify the speaker's gender based on spectral features of her/his voice. Typical recognition schemes work with utterances.…”
Section: Related Workmentioning
confidence: 99%
“…Để nhận dạng cảm xúc cho tiếng nói thu âm từ một tổng đài trả lời tự động, Laurence Vidrascu [5] sử dụng máy hỗ trợ véc tơ SVM và mô hình cây logic (LMT: Logistic Model Tree). Kalyana Kumar Inakollu [11], sử dụng mô hình hỗn hợp Gauss đa thể hiện (GMM: Gaussian Mixture Model) với tiếng nói đƣợc mô hình hóa bởi các hệ số theo thang tần số Mel (MFCC: Mel Frequency Cepstral Coefficients) [12]. Thurid [16] sử dụng thông tin về giới tính để cải thiện hiệu năng của hệ thống nhận dạng cảm xúc.…”
unclassified